Revitalizing the Bahtsul Masail Method to Foster Critical Thinking and Problem-Solving Skills Among Students in the Society 5.0 Era - Adelia Putri; Mawaddah Hidayati; Akwam (Sustainable, 2025)
The transition to Society 5.0 demands higher-order thinking skills, yet conventional pedagogies often fall short in addressing complex, ill-structured problems. This study aims to conceptualize the revitalization of the traditional Bahtsul Masail (BM) method to effectively foster critical thinking and problem-solving skills in this new era. Employing a qualitative literature review, data were systematically retrieved from the Google Scholar database (2020-2025) and analyzed through thematic coding and conceptual synthesis. The findings reveal that while traditional BM inherently aligns with advanced cognitive processes, its classical confinement limits contemporary relevance. The proposed revitalization expands the inquiry scope to socio-technological dilemmas, integrates empirical big data, and leverages digital collaborative platforms. Furthermore, it anchors problem-solving in Maqashid Syariah to ensure human-centric outcomes. Ultimately, the revitalized BM transforms from a classical jurisprudential exercise into a dynamic, ethically grounded incubator for 21st-century competencies. This modernized framework provides actionable insights for educators and policymakers seeking to cultivate future-ready graduates, successfully bridging Islamic intellectual heritage with the cognitive and moral demands of Society 5.0.